New role of biomarkers: mid-regional pro-adrenomedullin, the biomarker of organ failure - Valenzuela-Sánchez, Francisco; Valenzuela-Méndez, Blanca; Rodríguez-Gutiérrez, Juan Francisco; Estella-García, Ángel; González-García, María Ángela (Annals of Translational Medicine, 2016)
Mid-regional pro-adrenomedullin (MR-proADM) has a good biomarker profile: its half-life is several hours, and its plasma concentrations can be determined in clinical practice, it is essentially irrelevant, but proportionally represents the levels and activity of adrenomedullin (ADM). ADM synthesis is widely distributed in tissues, including bone, adrenal cortex, kidney, lung, blood vessels and heart. Its fundamental biological effects include vasodilator, positive inotropic, diuretic, natriuretic and bronchodilator. It has been described high levels in septic patients, interacting directly with the relaxation of vascular tone, triggering hypotension of these patients. It is also found high levels in other diseases such as hypertension, heart failure, respiratory failure, renal failure, cirrhosis and cancer. MR-proADM has been identified as a prognostic marker, stratifying the mortality risk in patients with sepsis in emergency department (ED) and ICU. Evolutionary MR-proADM levels and clearance marker to the 2nd–5th days of admission help to determine the poor performance and the risk of mortality in patients with severe sepsis admitted to the ICU. The MR-proADM levels are more effective than procalcitonin (PCT) and C-reactive protein (CRP) levels to determine an unfavorable outcome and the risk of mortality in patients with sepsis admitted to the ICU. It has also proved useful in patients diagnosed with organ dysfunction of infectious etiology. MR-proADM levels are independent of the germ conversely it is related to the magnitude of organ failure and therefore severity. We consider advisable incorporating the MR-proADM the panel of biomarkers necessary for the diagnosis and treatment of critically ill patients admitted to the ICU with severe sepsis. The combined PCT and MR-proADM levels could represent a valid tool in the clinical practice to timely identify patients with bacterial infections and guide the diagnosis and treatment of sepsis and septic shock.